Impact of a clinical pathway for relieving severe post-operative pain at a university hospital in South America (2013)
ABSTRACT: Background: Many patients experience severe Post-Operative Pain (POP) worldwide despite current advances in pain management. The clinical pathway for pain management is a strategy that has shown positive results for relieving pain and other negative outcomes, such as cardiovascular and respiratory complications associated with uncontrolled POP. It consisted in a series of steps to be followed by surgeon and medical staff related with surgical patients. Involved interventions during preoperative evaluation, post anesthesia care unit (PACU), and first three postoperative days. This study evaluated the efficacy of a clinical pathway for relieving severe pain in post-operative patients who underwent orthopedic, abdominal, and thoracic surgeries. Methods: The intervention involved implementation of educational workshops about multimodal and rescue analgesia for physicians and nurses, as well as implementation of measures to monitor POP and analgesia side effects. Two different groups of patients were assessed at 24 hours after surgery using a Verbal Numeric Scale (VNS) for pain intensity. 112 patients were interviewed before the clinical pathway was instituted (Group 1) and 110 patients after its implementation (Group 2). The main outcome was the frequency of severe POP, measured with VNS. Secondary outcomes were Quality of Recovery (QoR) and side effects such as nausea, vomiting, and epigastric pain. Results: This work showed a statistically significant decrease in severe POP frequency (p=0.003) and QoR improvement in Group 2 compared to Group 1 (mean: 61.5±5.0 vs 59.7±5.4, p=0.01). No significant differences in side effects or respiratory depression were observed in either group. Conclusion: This study demonstrates that implementation of a clinical pathway can bring benefits to patients with POP.